Antioxidative, antifungal and additive activity of the antimicrobial peptides leg1 and leg2 from chickpea - Heymich, Marie-Louise; Nißl, Laura; Hahn, Dominik; Noll, Matthias; Pischetsrieder, Monika (Foods, 2021)
The fight against food waste benefits from novel agents inhibiting spoilage. The present study investigated the preservative potential of the antimicrobial peptides Leg1 (RIKTVTSFDLPALRFLKL) and Leg2 (RIKTVTSFDLPALRWLKL) recently identified in chickpea legumin hydrolysates. Checkerboard assays revealed strong additive antimicrobial effects of Leg1/Leg2 with sodium benzoate against Escherichia coli and Bacillus subtilis with fractional inhibitory concentrations of 0.625 and 0.75. Additionally, Leg1/Leg2 displayed antifungal activity with minimum inhibitory concentrations of 500/250 µM against Saccharomyces cerevisiae and 250/125 µM against Zygosaccharomyces bailii. In contrast, no cytotoxic effects were observed against human Caco-2 cells at concentrations below 2000 µM (Leg1) and 1000 µM (Leg2). Particularly Leg2 showed antioxidative activity by radical scavenging and reducing mechanisms (maximally 91.5/86.3% compared to 91.2/94.7% for the control ascorbic acid). The present results demonstrate that Leg1/Leg2 have the potential to be applied as preservatives protecting food and other products against bacterial, fungal and oxidative spoilage.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Antifungal activity; Antimicrobial peptides; Antioxidative peptides; Chickpea peptides; Cytotoxicity; Leg1; Leg2